THE RELEVANCE OF HEALTH CULTURE DEVELOPMENT AS THE BASE FOR HIV AND AIDS PREVENTION - Сергей Николаевич Филимонов; Андрей Георгиевич Петров; Ольга Владимировна Хорошилова; Виктор Андреевич Семенихин (Медицина в Кузбассе)
Health culture includes a process of developing and maintaining of a relationship between a patient and a doctor, which is on the one hand built upon reliable information about a patient’s disease, and, on the other hand, on providing sustainable and constructive professional work between pharmacists and medical experts in order to improve a patient’s quality of life. Apart from demonstrating some HIV patients’ cases, the article discusses the ways of maintaining their physical and emotional health, their adaptation to the society and social questions of the HIV prevention.